Examining the Effect of Globalization on Insurance Activities in Large Emerging Market Economies - Olasehinde-Williams, Godwin; Balcilar, Mehmet (Elsevier, 2020)
This study applies the cross-sectionally augmented distributed lag long-run estimation technique alongside bootstrap panel Granger causality testing to examine the impact of globalization on insurance market activities in large emerging market economies. Economic, social and political globalization indices are considered separately. Two alternative measures of globalization (de facto and de jure) are also used in each case for our estimations. The empirical results confirm the following; first, empirical outcomes are slightly sensitive to the choice of globalization measure used. Second, cross-sectional dependence and cross-country heterogeneity exist among large emerging market economies. Third, causality varies across large emerging economies with different conditions. We make a case for de facto measures as the most appropriate since they reflect actual practices rather than policy claims. We thus reach the conclusion that all dimensions of globalization positively impact life and non-life insurance density.
Keywords: Globalization; Insurance Markets; CS-DL; Bootstrap panel Granger causality; Large Emerging Market Economies